Smart cities in the Mediterranean : coping with sustainability objectives in small and medium-sized cities and island communities - Stratigea, Anastasia; Kyriakides, Elias; Nicolaides, Chrysses (Springer Science and Business Media : Springer, 2017)
This book sheds new light on the current and future challenges faced by cities, and presents approaches, options and solutions enabled by Information and Communication Technologies (ICT) in the smart city context. By focusing on sustainability objectives within a rapidly changing social, economic, environmental and technological setting, it explores a variety of planning challenges faced by contemporary cities and the power of smart city developments in terms of providing innovative tools, approaches, methodologies and technologies to help cities cope with these challenges. Key issues addressed include smart city (e- ) planning and (e- )participation; smart data management to facilitate decision-making processes in cities and insular communities on a variety of topics; smart and sustainable management aspects of climate change, water scarcity, mobility, energy, infrastructure, tourism, blue growth, risk assessment; etc.
Keywords: Business.; Industrial management -- Environmental aspects.; Information technology.; Business -- Data processing.; Regional planning.; City planning.; Architecture.; Sustainable development.; elektronické knihy; electronic books